The set of fuzzy points of coalgebras - Chen, Wenjuan,; Guan, Yanyong, (Utilitas Mathematica, 2012)
In this paper we proved that the set of fuzzy points of a coalgebra is a coalgebra and showed that there is a one-to-one correspondence between the fuzzy subcoalgebras and certain crisp subcoalgebras.